Vertically aligned N-doped CNTs growth using Taguchi experimental design - Silva, Ricardo M
tThe Taguchi method with a parameter design L9orthogonal array was implemented for optimizing thenitrogen incorporation in the structure of vertically aligned N-doped CNTs grown by thermal chemicaldeposition (TCVD). The maximization of the ID/IGratio of the Raman spectra was selected as the targetvalue. As a result, the optimal deposition configuration was NH3= 90 sccm, growth temperature = 825◦Cand catalyst pretreatment time of 2 min, the first parameter having the main effect on nitrogen incorpo-ration. A confirmation experiment with these values was performed, ratifying the predicted ID/IGratioof 1.42. Scanning electron microscopy (SEM) characterization revealed a uniform completely verticallyaligned array of multiwalled CNTs which individually exhibit a bamboo-like structure, consisting ofperiodically curved graphitic layers, as depicted by high resolution transmission electron microscopy(HRTEM). The X-ray photoelectron spectroscopy (XPS) results indicated a 2.00 at.% of N incorporation inthe CNTs in pyridine-like and graphite-like, as the predominant species.